Instructors' Attitudes towards Applying Effective Technique in Teaching Reading Skill (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study aims at investigating the instructors' attitudes towards applying effective technique teaching reading skill. The study adopted the descriptive method. A questionnaire is used as a primary tool for data collection. Population of the study is teachers of English at different Sudanese Universities. The sample of study drawn from the consisted of 50 teachers who were selectedrandomly. This study used the statistical package for social science (SPSS) program to analyze and verify the hypotheses. The results showed that instructors encourage students to relate their background knowledge about the topic of the reading. Furthermore, instructors prefer to direct students in identifying the main ideas of what they have read. The study recommended that Instructorsshould ask students to make predictions about what will happen next in the text they are reading. Moreover, instructors should be well-trained in using effective technique in teaching reading skill.
Keywords: dynamically; substantial; schematic; comprehending; synthesize